Hieroglyphics - McCorkle, Jill, 1958- (Algonquin Books of Chapel Hill, 2020)
"Lil and Frank married young, having bonded over how they both lost a parent when they were children. Over time, their marriage grew and strengthened, with each still wishing for so much more understanding of the parents they'd lost prematurely. Now, after many years in Boston, they have retired in North Carolina. There, Lil, determined to leave a history for their children, sifts through letters and notes and diary entries - perhaps revealing more secrets than Frank wants their children to know. Meanwhile, Frank has become obsessed with what might have been left behind at the house he lived in as a boy on the outskirts of town, where a young single mother, Shelley, is just trying to raise her son with some sense of normalcy. Frank's repeated visits to Shelley's house begin to trigger memories of her own family, memories that she'd rather forget. Because, after all, not all parents are ones you wish to remember"--Provided by publisher.